Plant photosynthetic overcompensation under nocturnal warming: lack of evidence in subtropical evergreen trees. (11th June 2022) - Du, Ying; Lu, Ruiling; Sun, Huanfa; Cui, Erqian; Yan, Liming; Xia, Jianyang
Abstract: Background and Aims: Increased plant photosynthesis under nocturnal warming is a negative feedback mechanism to overcompensate for night-time carbon loss to mitigate climate warming. This photosynthetic overcompensation effect has been observed in dry deciduous ecosystems but whether it exists in subtropical wet forest trees is unclear. Methods: Two subtropical evergreen tree species ( Schima superba and Castanopsis sclerophylla ) were grown in a greenhouse and exposed to ambient and elevated night-time temperature. The occurrence of the photosynthetic overcompensation effect was determined by measuring daytime and night-time leaf gas exchange and non-structural carbohydrate (NSC) concentration. Key Results: A reduction in leaf photosynthesis for both species and an absence of persistent photosynthetic overcompensation were observed. The photosynthetic overcompensation effect was transient in S. superba due to respiratory acclimation and stomatal limitation. For S. superba, nocturnal warming resulted in insufficient changes in night-time respiration and NSC concentration to stimulate overcompensation and inhibited leaf stomatal conductance by increasing the leaf-to-air vapour pressure deficit. Conclusions: The results indicate that leaf stomatal conductance is important for the photosynthetic overcompensation effect in different tree species. The photosynthetic overcompensation effect under nocturnal warming may be a transient occurrence rather than a persistent mechanism in subtropical forest ecosystems.